Education Policy 2023 – 2027 - Trinidad and Tobago. Ministry of Education (Ministry of Education, Trinidad and Tobago, 2023)
This Education Policy serves to guide the actions of the Ministry over a five-year period in advancing the cause of education while addressing current challenges within the education sector of Trinidad and Tobago. This Policy reflects not only the national development agenda, but also the commitment to regional and international prerogatives in the achievement of the 2030 Agenda for Sustainable Development by all United Nations Member States. In concert with the United Nations Sustainable Development Goals, the key educational thrusts identified for the CARICOM region are inclusive education; equitable education; quality education and the promotion of lifelong learning. The methodology adopted for developing this Education Policy involved consultations with key stakeholders in education through focus group discussions and interviews; review of national, regional and international reports; analysis of policy documents of various countries; environmental scanning and analysis of quantitative data from the Ministry of Finance on estimates of expenditure. Key stakeholders included teachers, students, parents, specialists in the field and members of the community. Critical inputs also came from various Divisions/Units of the Ministry as well as stakeholder groups such as the National Parent Teacher Association (NPTA), Principals’ Associations, Denominational Boards, the Trinidad and Tobago Unified Teachers’ Association (TTUTA), tertiary education institutions and other stakeholder groups.
Keywords: education policy